Evidence on postoperative abdominal binding: A systematic review with meta-analysis of randomized controlled trials. Issue 4 (August 2021) - Ossola, Paolo; Mascioli, Federico; Coletta, Diego; Pizzato, Margherita; Bononi, Marco
Abstract: Background: Midline laparotomy is an unavoidable approach to many surgical procedures. Many surgeons prescript the use of postoperative abdominal binder during the first mobilization after surgery. The use and the cost effective of this device is still debated by many surgeons. Methods: PubMed, EMBASE and the CENTRAL were systematically searched for randomized controlled trials (RCT) comparing patients who wore abdominal binder ("binder") and patient who did not wear any abdominal binder ("non-binder") up to March 2020. The primary outcomes measured in the comparison were postoperative pain, pulmonary functions, the entity of physical activity, the comfort. A meta-analysis of relevant studies was performed using RevMan 5.3. Results: wearing an abdominal binder after midline laparotomy seems to reduce postoperative pain on first and third postoperative day, to improve the physical activity on third postoperative day, and not affect pulmonary functions. Generally, an elastic abdominal binder is well tolerated during postoperative. Conclusions: the use of elastic abdominal binder permits a comfortable early postoperative mobilization reducing pain, increases physical activity and seems to not affect pulmonary functions. Highlights: Laparotomy is an unavoidable surgical procedure, even today. The indications to wear a postoperative abdominal binder are not clear. The use of postoperative abdominal binder reduces the postoperative pain. Wearing a postoperative abdominal binder could improve the postoperative rest.